Asylum seekers' Occupy movement in Hong Kong. (October 2014) - Vecchio, Francesco; Beatson, Cosmo
This piece offers preliminary reflections on the theoretical justification of a highly organised protest staged against the non-profit organisation contracted by the Hong Kong Government to provide asylum seekers with humanitarian assistance. In so doing, it reveals the central role played by asylum seekers reacting to border policies and practices that cause their immiseration.